Urban afforestation as a bioindicator of atmospheric mercury pollution: a case study with Moquilea tomentosa Benth. (Chrysobalanaceae) in the southern region of the Amazon (Research, Society and Development, 2022)
Mercury (Hg) is internationally considered a global pollutant and has a high rate of dispersion from its emission sources, due to atmospheric transport. Considering that this metal comes from both natural and anthropogenic sources, it is important to know how much Hg are emitted, the concentrations observed in the environment and estimate its impacts on human health and ecosystems. Thus, this study evaluated the presence of mercury in the urban perimeters of six municipalities in the northern region of Mato Grosso, southern Amazon, using leaves of the tree species Moquilea tomentosa Benth. (Chrysobalanaceae) widely used in urban afforestation in this region. The results showed significant differences in mercury concentrations between the evaluated municipalities (ANOVA = p≤ 0.0001), evidencing the presence of this heavy metal in the atmosphere in all evaluated urban perimeters. The highest mean Hg value was observed in Paranaíta (172.8 µg Kg-1), followed by Alta Floresta (62.1 µg Kg-1), Carlinda (52.3 µg Kg-1), Nova Canaã do Norte (25.5 µg Kg-1), Colíder (19.3 Kg-1) and Nova Santa Helena (6.8 µg Kg-1). However, all these concentrations are within the range considered acceptable. Thus, the use of M. tomentosa were recommended as an indicator of atmospheric mercury deposition in urban areas, with the need for studies following a time series allowing the establishment of specific protocols for different types of atmospheric pollutants.